Using the Five Core Components of Competency-Based Medical Education to Support Implementation of CBVE - Chaney, Kristin P.; Hodgson, Jennifer L. (Frontiers in Veterinary Science, 2021)
In recent years, veterinary education has begun the transition to competency-based models, recognizing that, like medical education, our goals include improved patient and client outcomes and the importance of learner-centered methods in education. Given that implementation of competency-based veterinary education (CBVE) is still in its relative infancy across many veterinary programs, we stand to gain from a unified approach to its implementation. As a guideline, the five core components of competency-based medical education (CBME) should serve to ensure and maintain fidelity of the original design of outcomes-based education during implementation of CBVE. Identified the essential and indispensable elements of CBME which include 1) clearly articulated outcome competencies required for practice, 2) sequenced progression of competencies and their developmental markers, 3) tailored learning experiences that facilitate the acquisition of competencies, 4) competency-focused instruction that promotes the acquisition of competencies, and 5) programmatic assessment. This review advocates the adoption of the principles contained in the five core components of CBME, outlines the approach to implementation of CBVE based upon the five core components, and addresses the key differences between veterinary and medical education which may serve as challenges to ensuring fidelity of CBVE during implementation.